Compression Characteristics and Constitutive Model of Low-Exotherm Modified Polyurethane Grouting Materials - Shengjie Xu; Shuangjie Wang; Yanhui Zhong; Bei Zhang; Juan Zhang; Yanjun Wang; Liguo Zhao (Advances in Civil Engineering)
In permafrost regions, ordinary polyurethane grouting materials are not suitable for the repair and reinforcement of road engineering due to the release of a large amount of heat during the reaction process. In this study, the polyurethane grouting material is modified by changing the catalyst, blowing agent, and reaction scheme to reduce the heat released during the reaction. The stress-strain curves of low-exotherm polyurethane grouting material specimens possessing various densities are investigated by means of unconfined uniaxial compression experiments, and the stress-strain relationships and failure mode of low- and high-density specimens are analysed. The characteristics of three stages in the compression process of the materials, namely, the elasticity stage, platform stage, and densification stage, are studied. The compressive strength increases with the increase in density, and the brittle failure of materials with higher density is more obvious. From the microscopic point of view, combined with the experimental results, the constitutive model of low-exotherm modified polyurethane grouting material was established. The established model is in good agreement with the experimentally measured stress-strain curves and effectively predicted the stress-strain characteristics for a specimen possessing a different density.